2008
DOI: 10.1088/0031-9155/53/24/008
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of relative biological effectiveness of a low-energy electronic brachytherapy source

Abstract: Low-energy x-rays are known to have a higher relative biological effectiveness (RBE) than higher energy photons such as the gamma rays from 192Ir and 60Co. In this work the initial yield of single- and double-strand DNA breaks (SSB and DSB) and the RBE was estimated for a novel electronic brachytherapy source (EBS), emitting 40-50 kVp photons. An EGSnrc Monte Carlo model of the source was used in combination with the 'Monte Carlo damage simulation' program (Semenenko and Stewart 2004 Radiat. Res. 161 451-57; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 34 publications
8
42
1
Order By: Relevance
“…Thus, photons emitted in a treatment with Esteya ® have considerably lower energy than photons emitted by a 192 Ir source. It has been reported that lower energy photons have a higher radiobiological effectiveness (RBE) [17]. This implies that a lower physical dose should be prescribed with EBT sources in order to achieve the same clinical results (i.e.…”
Section: Rationale For the Study Fractionation Schedulesmentioning
confidence: 99%
“…Thus, photons emitted in a treatment with Esteya ® have considerably lower energy than photons emitted by a 192 Ir source. It has been reported that lower energy photons have a higher radiobiological effectiveness (RBE) [17]. This implies that a lower physical dose should be prescribed with EBT sources in order to achieve the same clinical results (i.e.…”
Section: Rationale For the Study Fractionation Schedulesmentioning
confidence: 99%
“…2, chargedparticle stopping power in water is equated to the stopping power of an a particle with the same (Z eff /b) 2 . For photons, the MCDS computes a fluence-averaged stopping power from the spectrum of secondary electrons arising when the (primary) photon first interacts in or near the cell nucleus (61,62). The MCDS also has the capability to estimate the fluence-averaged stopping power for a mixture of ions with the same or different kinetic energy.…”
Section: 200mentioning
confidence: 99%
“…Because of the low photon energy of EB, the difference in the biologic effectiveness of EB and the HDR technique also needs to be considered. It is well established that the relative biologic effectiveness (RBE) of photons increases with decreasing photon energy, corresponding to the increase in the linear energy transfer (27)(28)(29)(30)(31)(32)(33)(34)(35). Therefore, not surprisingly, RBE values in the range of 1.50-1.62 for 40 to 50 kV X-rays (0.0-0.7 mm Al filters) relative to 60 Co g-rays were measured for the 10% survival of V79 cells (Chinese hamster cells) (30).…”
Section: Discussionmentioning
confidence: 99%